Production of a functional cell wall-anchored minicellulosome by recombinant Clostridium acetobutylicum ATCC 824. Issue 1 (December 2016) - Willson, Benjamin; Kovács, Katalin; Wilding-Steele, Tom; Markus, Robert; Winzer, Klaus; Minton, Nigel
Abstract Background The use of fossil fuels is no longer tenable. Not only are they a finite resource, their use is damaging the environment through pollution and global warming. Alternative, environmentally friendly, renewable sources of chemicals and fuels are required. To date, the focus has been on using lignocellulose as a feedstock for microbial fermentation. However, its recalcitrance to deconstruction is making the development of economic processes extremely challenging. One solution is the generation of an organism suitable for use in consolidated bioprocessing (CBP), i.e. one able to both hydrolyse lignocellulose and ferment the released sugars, and this represents an important goal for synthetic biology. We aim to use synthetic biology to develop the solventogenic bacteriumC. acetobutylicum as a CBP organism through the introduction of a cellulosome, a complex of cellulolytic enzymes bound to a scaffold protein called a scaffoldin. In previous work, we were able to demonstrate the in vivo production of aC. thermocellum -derived minicellulosome by recombinant strains ofC. acetobutylicum, and aim to develop on this success, addressing potential issues with the previous strategy. Results The genes for the cellulosomal enzymes Cel9G, Cel48F, and Xyn10A fromC. cellulolyticum were integrated into theC. acetobutylicum genome using Allele-Coupled Exchange (ACE) technology, along with a miniscaffoldin derived fromC. cellulolyticum CipC. The possibility of anchoring the recombinant cellulosome to the cell surface using the native sortase system was assessed, and the cellulolytic properties of the recombinant strains were assayed via plate growth, batch fermentation and sugar release assays. Conclusions We have been able to demonstrate the synthesis and in vivo assembly of a four-component minicellulosome by recombinantC. acetobutylicum strains. Furthermore, we have been able to anchor a minicellulosome to theC. acetobutylicum cell wall by the use of the native sortase system. The recombinant strains display an improved growth phenotype on xylan and an increase in released reducing sugar from several substrates including untreated powdered wheat straw. This constitutes an important milestone towards the development of a truly cellulolytic strain suitable for CBP.